Sobre a presencia de Parabemisia myricae (Kuwana) (Homoptera; Aleyrodidae) en Portugal - Franco, J.C.=700 1 Cavaco, M.; Carvalho, J.C.; Fernandes, J.C.
(En, Es)
ilus., 51 ref.
Keywords: PARABEMISIA; CITRUS; PORTUGAL